Are we asking the right questions? Female athletes` perspectives on the menstrual cycle in sport - van den Berg, C. A.; Doyle-Baker, P. K. (Psychology of Sport and Exercise, 2025)
Background Menstrual cycle (MC) research employing qualitative and quantitative methods has recently increased in athlete populations. A move towards a participant-centered approach to help formulate questions that align with practitioners` and stakeholders` priorities in the sport environment is needed. Therefore, our study aims were to 1) understand what athletes feel is important to consider regarding their MC in sport and, 2) provide practical recommendations for coaches and practitioners to support a positive sport culture around the MC.